Biblia : Stary i nowy testament - Dore, Gustave, 1832-1883 (Warszawa : Wydawnictwo Artystyczne i Filmowe, 1991)
Selected Bible passages with appropriate illustrations.
Bible passages are taken from the 3rd rev. ed. of the Biblia Tysiaclecia (Warszawa, Poznan : Pallotinum, 1984) -- p. [6].
Alternate pages of selections from the Bible and illustrations.
Invalid ISBN on the dust jacket: 83-221-0519-2.